2017
DOI: 10.1080/0142159x.2017.1406903
|View full text |Cite
|
Sign up to set email alerts
|

Peer group reflection on student ratings stimulates clinical teachers to generate plans to improve their teaching

Abstract: Peer group reflection on student ratings shows promise as tool to assist clinical teachers in generating plans for improvement. Future research should focus on whether teaching indeed improves with the introduction of peer group reflection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…Furthermore, this study found that interaction with others was crucial for secondary school students to engage in critical reflection. On the one hand, this study confirmed that interaction with peers can help young learners reflect critically and come up with more alternative plans [54,55]. The different opinions of their peers led the students to re-examine their own learning process and perspectives.…”
Section: Perceptions Of Integrating Critical Reflection Into Ct Educationsupporting
confidence: 67%
“…Furthermore, this study found that interaction with others was crucial for secondary school students to engage in critical reflection. On the one hand, this study confirmed that interaction with peers can help young learners reflect critically and come up with more alternative plans [54,55]. The different opinions of their peers led the students to re-examine their own learning process and perspectives.…”
Section: Perceptions Of Integrating Critical Reflection Into Ct Educationsupporting
confidence: 67%
“…Thus, future iterations of the course will include individual and group assessments for self-reflection and to incentivize student participation in the team activities ( Jacobs et al. , 2013 ; van Lierop et al. , 2018 ; Carrasco et al.…”
Section: Discussionmentioning
confidence: 99%
“…17 Several authors have indicated that peers can be viewed as instructional resources for one another as they share learning intentions and criteria for success. [18][19][20][21] Finally, sharing personal reflections with colleagues could improve the quality of collegial relationships and increase the chance of real performance improvement. 15 The question arises whether and how group sessions are helpful for physicians to reflect on their professional performance and contribute to their development.…”
Section: Discussionmentioning
confidence: 99%
“…17 Several authors have indicated that peers can be viewed as instructional resources for one another as they share learning intentions and criteria for success. 18–21 Finally, sharing personal reflections with colleagues could improve the quality of collegial relationships and increase the chance of real performance improvement. 15…”
mentioning
confidence: 99%